Analisis Kepatuhan Apotek Dalam Penyerahan Antibiotik Berdasarkan Resep Dokter Sebelum Dan Sesudah Implementasi Surat Edaran Kepala Daerah: Studi Monitoring Bpom Di Bengkulu - Novri Fitriani; Avrilya Iqoranny Susilo (Jurnal Pharmacopoeia, 2026)
Antimicrobial resistance (AMR) is a growing health threat and has the potential to increase morbidity, mortality, and the economic burden on health care. One of the main factors driving the development of AMR is the irrational use of antibiotics, including the practice of dispensing antibiotics without a doctor's prescription in pharmaceutical service facilities. To strengthen control of antibiotic use, the regional government issued a Regional Head Circular (SE) which emphasized that antibiotics may only be dispensed with a doctor's prescription. This study aims to analyze the results of BPOM monitoring of antibiotic dispensing compliance at pharmacies in Bengkulu Province before and after the issuance of the Regional Head Circular. This study used a quasi-experimental design with a before-after study approach based on BPOM monitoring data at the same 42 pharmacies in Bengkulu Province in 2024 and 2025. The analysis was conducted descriptively and comparatively using the McNemar test for paired data with a significance level of p < 0.05. The results showed that before the Circular was implemented, only 3 pharmacies (7.1%) complied with dispensing antibiotics with a doctor's prescription, while 39 pharmacies (92.9%) still dispensed antibiotics without a prescription. After the issuance of the circular, 16 pharmacies (38.1%) were compliant, while 26 pharmacies (61.9%) remained non-compliant. The McNemar test showed a significant difference between the two periods. The issuance of the Regional Head's circular was associated with increased pharmacy compliance in dispensing antibiotics based on doctor's prescriptions